Problems and Prospects of High Employee Turnover in Kurdistan Hospitality Sector - Agwu, Mba Okechukwu; Makki, Ashti (Archives of Business Research, 2023)
The paper discussed problems and prospects of high employee turnover in Kurdistan hospitality sector. It assumes that organizational factors such as commitment, engagement, satisfaction and compensation could affect employee turnover in Kurdistan hospitality sector. The research question addressed the extent to which low wages, poor working conditions, communication barrier between management and staff and lack of employee training/development contributed to high rate of employee turnover in the Kurdistan hospitality sector. The core aspect of the study is the use of cross-sectional survey research design in generating the required primary data. The place of study is Kurdistan hospitality sector while the duration of study is between December 2021and November 2022. A sample of 364 (75 managers, 1319 supervisors and 1857workers) respondents determined at 5% level of significance for sample error, using Yamane’s formula was selected from a population of 4,000 employees in Kurdistan hospitality sector using stratified random sampling method for the purpose of questionnaire administration. The results indicated that low wages, poor working conditions, communication barrier between management and staff and lack of employee training/development contributed to a large extent to high rate of employee turnover in Kurdistan hospitality sector. It therefore recommends among others: change in work-life balance, effective talent management, better employee reward, employee mentoring and effective communication as strategies of reducing high employee turnover in Kurdistan hospitality sector.